Plant functional group has stronger effects on soil functions than planting density: an examination with pot experiment - Jiao, Huan; Cao, Zhenrui; Gong, Lin; Chang, Xingchen; Fang, Chuanxu; Wang, Xiang; Li, Wenrao; Ishii, Satoshi; Kong, Weibo; Wei, Xiaorong (Frontiers in Plant Science, 2025)
IntroductionPlant functional groups (PFGs) and plant density are two important characteristics of plant community dynamics; however, the main and interactive effects of PFGs and plant density on ecosystem functions have not been thoroughly analyzed, limiting our ability to predict and manage ecological responses to community changes.MethodsA pot experiment was done with four PFGs (C3 grasses, C4 grasses, forbs, and legumes) and six planting density gradients (1, 2, 4, 8, 12, and 16 spots per pot) to evaluate how PFGs and plant densities influence plant biomass and soil functions, including nutrients, extracellular enzyme activity, microbial necromass carbon, and nitrogen mineralization rates, in rhizosphere and bulk soils.ResultsMost of the soil function metrics increased as planting density increased, and such effects were greater in rhizosphere soils than in bulk soils. The magnitude and direction of density effects varied among PFGs, indicating interactive effects. Legumes had stronger effects than the other PFGs on soil multifunctionality index, nitrogen mineralization rates, and aboveground biomass. Similarly, C3 grasses had the strongest effects on soil extracellular enzyme activities in rhizosphere soils among the four PFGs tested. ConclusionOur results suggest that plant functional group has stronger effects on soil functions than planting density.